Managing mental health in chronic care in general practice: a feasibility study of the Healthy Mind intervention - Anne Soejbjerg; Stinne Eika Rasmussen; Kaj Sparle Christensen; Bo Christensen; Anette Fischer Pedersen; Helle Terkildsen Maindal; Anna Mygind (Taylor & Francis Group, 2024)
AbstractBackground and objective Mental health issues are common among patients with chronic physical conditions. This study aims to evaluate the feasibility of the Healthy Mind intervention, a general practice-based programme that provides problem-solving therapy (PST) to patients with poor mental well-being and type 2 diabetes (T2D) and/or ischaemic heart disease (IHD).Design and setting A one-arm feasibility study was conducted in three general practices in the Central Denmark Region.Intervention Eight healthcare providers from the included general practices underwent a two-day course to acquire PST skills. Screening for poor mental health was carried out at the annual chronic care consultation for T2D or IHD, and PST sessions were offered to patients on indication of poor mental health. Nine patients received PST.Methods Semi-structured interviews with eight healthcare providers and six patients were conducted. Data were analysed deductively focusing on appropriateness, acceptability and fidelity of the intervention.Results The intervention was considered appropriate for the patient group and the general practice setting. The providers acknowledged PST as a valuable tool for managing psychological issues in general practice, and the patients perceived PST as an effective and tangible treatment. Since practice nurses' schedules were generally better suited for longer consultations, they were often the preferred intervention providers. The intervention was largely delivered as intended. However, the GPs generally expected patients to prefer a more directive approach, which sometimes challenged their role as facilitator and guide.Conclusion The Healthy Mind intervention was found to be feasible, and the results support proceeding to a full-scale evaluation trial.